POTENSI TEGAKAN DI KPHL BATU SERAMPOK, PROVINSI LAMPUNG - Sobirin Sobirin; Irwan Sukri Banuwa; Indra Gumay Febryano; Christine Wulandari; Arif Darmawan; Dian Iswandaru (Jurnal Hutan Tropis, 2022)
Data and information regarding the potential of forest stands is very important in the preparation of Long-Term Forest Management Plan at Forest Management Unit. The purpose of the study was to analyze the potential of stands in the Protected Forest Management Unit Batu Serampok. Data and information were collected using a stratified systematic sampling with random start inventory method, then vegetation was analyzed to obtain an index of importance. The results showed a diversity of potential stands. The species that predominate in the seedling phase are clove (Syzygium aromaticum), because the commodity is easily grown and liked by the community. The species that has the highest importance in the sapling phase is bayur (Pterospermum sp.), This is because the species is included in the semi-intolerant classification and its distribution is quite easy. In the pole phase, the dominant species are bayur and mango (Mangifera indica). The dominance of bayur has decreased in the pole phase due to changes in environmental conditions, adaptability and the presence of other plants developed by the community. Mango also have a fairly dominant number, as well as other types of Multi Purpose Tree Species (MPTS) plants. Then at the tree level, the dominant species include bayur, jengkol (Archidendron pauciflorum), teak (Tectona grandis), gondang (Ficus variegata), candlenut (Aleurites moluccana) and petai (Parkia speciosa). In this phase there has been a balance between species of wood forest and MPTS. This happened because of the intervention of the HKm group in determining the types of plants to be developed. The preparation of the RPHJP document in Forest Management Unit should pay attention to the types of plants that are dominant and preferred by the community, especially in the planning part of forest land reforestation program.